Edukasi Kesehatan dan Skrining Mandiri Berbasis Digital untuk Masyarakat dalam Peringatan Hari Kesehatan Nasional Tahun 2025 - Junios Junios; Delsi Kariman; Falerisiska Yunere; Yossi Fitrina; Meutia Askina; Arfezsa Ulfa Rizkina (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2025)
This community service initiative aims to enhance understanding of non-communicable disease (NCD) prevention, promote healthy lifestyles, and offer digital screening services. The implementation method included health education sessions, demonstrations of self-screening apps, and basic health checkups for 127 participants from various sub-districts. The results showed that 89% of participants gained a better understanding of NCD risk factors, 76% successfully used the digital screening app independently, and 52 participants (41%) were identified as being at moderate to high risk for hypertension and referred for follow-up at a health facility. This initiative demonstrated that a direct educational approach and digital technologies can empower the community to identify health risks independently. It is recommended that this action be integrated into the regular agenda of local authorities to strengthen community-level promotion and prevention efforts.